2017
DOI: 10.1021/acsami.7b12436
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Soluble Isoindigo Derivative IIDTh-NSB as a Novel Modifier of ZnO in Inverted Polymer Solar Cells

Abstract: Alcohol-soluble isoindigo derivative with thiophene groups and sulfobetaine zwitterions, IIDTh-NSB was applied as a novel modifier of ZnO in inverted polymer solar cells (i-PSCs). When IIDTh-NSB (0.2 mg/mL) was spin-coated on ZnO as an electron transport layer (ETL), power conversion efficiency (PCE) of the PTB7:PCBM based i-PSCs reached 8.88%, which is a 20% improvement of that of 7.40% for the device with the ZnO-only ETL. If ZnO was doped by IIDTh-NSB of 1.0 wt %, the PCE of 8.50% could be achieved in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…More than 30 devices for all device configurations were measured to ensure the validity and repeatability of data. Device 1 displays an average PCE of 7.31% comparable to the reported values by others under similar conditions . When the ZnO was doped by AMF, simultaneous improvements in V OC , J SC , and FF have been observed in the i-PSCs.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…More than 30 devices for all device configurations were measured to ensure the validity and repeatability of data. Device 1 displays an average PCE of 7.31% comparable to the reported values by others under similar conditions . When the ZnO was doped by AMF, simultaneous improvements in V OC , J SC , and FF have been observed in the i-PSCs.…”
Section: Resultssupporting
confidence: 82%
“…Polymer solar cells (PSCs) have been widely investigated thanks to some particular features, for example, low cost, light weight, flexibility, solution processing, and the potential for fabricating large-area PSCs. Power conversion efficiency (PCE) has been quickly boosted via synthesis of original photoactive materials, modification of interface layers, morphology control of active layers, , and design of new device structures. , So far, a champion PCE value of 14.62% has been achieved in the ternary inverted PSCs (i-PSCs) . Recently, i-PSCs have been developed rapidly due to their higher PCE and better device stability than conventional PSCs .…”
Section: Introductionmentioning
confidence: 99%
“…The electron-deficient ID is an ideal unit for building D-A molecules and n-type semiconductors, suggesting that ID is an excellent central part of the development of CILs materials. [34,35] PFN-ID can be prepared at low temperature (105 °C) and is soluble in methanol solution after the addition of 0.3% acetic acid, which holds promise for a low-cost noninterfacial mixed solution method for the preparation of PSCs. The chemical and physical properties of the photovoltaic devices demonstrated that the incorporated PFN-ID can effectively inhibit charge recombination, decrease the WF of the cathode, and form an excellent ohmic contact at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…In order to study the exciton dissociation and charge collection properties of the devices with different cathode, we selectively investigated the J ph -V eff characteristics of the PM6:Y6 based NF-PSCs. 51,54 J ph presents the difference between photocurrent under the light (Figure 2a) and in the dark (Figure S7). As shown in Figure 3a, the J ph reached saturated photocurrent (J ph,sat ) when the V eff approached 2 V. J ph /J ph,sat ratios could estimate the probabilities of exciton dissociation and charge carrier collection.…”
Section: Resultsmentioning
confidence: 99%
“…46,47 Advantages of the TOASiW 12 over other organic CIL materials for large-area production of the PSCs are evident because of its low-cost (< $1/g), simple, green (solvents: alcohol and water) and high-yield (> 90%) synthetic procedures. [48][49][50] Compared to ZnO, 51 it does not require thermal annealing and has better adhesion and compatibility with the active layer due to introducing sixteen flexible alkyl chains. In addition, TOASiW 12 is more environmentally friendly than ZrAcAc.…”
Section: Introductionmentioning
confidence: 99%